The development of a recommended digital marketing strategy for Pan Macmillan, South Africa - Conradie, Tessa Jane (Rhodes University, Faculty of Commerce, Rhodes Business School, 2016)
This research attempts to create a recommended digital marketing strategy for Pan Macmillan, South Africa. As a result of the advance of technology and the increase of connectivity, digital marketing is becoming a highly important tool with regards to competitive advantage, differentiation and the overall marketing of a company and its product or service (Barwise and Farley, 2005, p. 68). Digital marketing is, in South Africa specifically, a relatively new concept (Sandmann, 2014, p. 1). If South African companies are able to efficiently utilise the gap in the market, they will ensure a significant competitive advantage (Sandmann, 2013, p. 1). In order to accomplish this successfully a digital marketing strategy must be created and adopted to ensure a full understanding of the requirements of effective digital marketing. This research focusses on understanding digital marketing requirements in relation to a South African book publisher and how those requirements can be met by the publisher through the development of a digital marketing strategy. The literature has been reviewed and previous research indicates that an established framework is needed to guide the development of a digital marketing strategy. The framework used in this research is the RACE framework (Chaffey and Bosomworth, 2013, p. 14) which is used in conjunction to the SOSTAC planning system (Chaffey and Bosomworth, 2014, p. 11) and the 7 steps to digital marketing strategy creation (Chaffey and Bosomworth, 2014, p. 2). The literature suggests that a combination of the established traditional marketing strategy of a company and current digital marketing practices and tools is the most practical with regards to the development of a successful digital marketing strategy, implementation and evaluation. In order to understand the current marketing strategy and practices of Pan Macmillan, interviews with the Marketing Manager of the company were conducted as well as an analysis of marketing documents relating to Pan Macmillan's current marketing actions. Results of the interviews and documentation analysis showed that Pan Macmillan had many elements digital marketing but no decisive digital marketing strategy. Using the selected frameworks and information gathered on the company's marketing practices, digital marketing goals were established and a digital marketing strategy was created. The goals of the research were reached as a recommended digital marketing strategy was developed for Pan Macmillan based on the assessment made, using RACE, SOSTAC and the 7 steps to digital marketing creation, of the company's current practices, challenges and opportunities with regards to digital marketing.
Keywords: Uncatalogued